Reorientation of the Education Quality Assurance System in Indonesia: Integration of Village Potential, Social Capital, and Participatory Governance in Improving the Quality of National Education - Nanang Hermawan (PT. Pusmedia Group Indonesia, 2026)
The Education Quality Assurance System in Indonesia is still dominated by administrative and centralistic approaches, making it less responsive to the local context, especially in rural areas that face inequality in the quality of education. In fact, villages have strategic potential in the form of social capital, local wisdom, and community participation which has the opportunity to become an alternative foundation for the development of national education quality. This study aims to analyze the urgency of reorienting the Education Quality Assurance System in Indonesia through the integration of village potential, social capital, and participatory governance in an effort to improve the quality of inclusive and sustainable education. This study uses a descriptive qualitative method based on a literature study on primary and secondary sources related to quality assurance policies, community-based education, and village development, which was studied from July to October 2025. The literature search process was conducted systematically on publications from 2015–2025 through academic databases such as Scopus, Web of Science, Google Scholar, ERIC, and SINTA-indexed journals. The selection of literature was carried out purposively by prioritizing peer-reviewed publications, internationally reputable journals, policy documents, and studies with strong relevance to education quality assurance, social capital, participatory governance, and rural education development. The objects of the study include national education quality assurance policies, educational practices in rural areas, and the role of village communities in quality management. Data analysis is carried out through data reduction, thematic categorization, and critical interpretation with policy and sociological approaches. The results of the study show that the integration of village potential and social capital can strengthen a contextual culture of education quality, increase the relevance of education to local needs, and encourage accountability and public participation. However, limited institutional capacity and bureaucratic resistance remain major challenges. This research emphasizes the importance of the community-based education quality assurance paradigm with villages as strategic actors of national education quality.